Improving Access to Care for Women Veterans Suffering from Chronic Pain and Depression Associated with Trauma. Issue 7 (9th May 2013) - Tan, Gabriel; Teo, Irene; Srivastava, Devika; Smith, Donna; Smith, Shirley L.; Williams, Wright; Jensen, Mark P.
Abstract Objective Access to care has become a priority for the Veterans Administration (VA) health care system as a significant number of veterans enrolled in the VA health care system reside in rural areas. The feasibility and effects of a novel clinical intervention that combined group therapy and biofeedback training was evaluated on women veterans living in rural areas. Methods The study was conducted at selected community‐based outpatient clinics (CBOCs) in Texas. Thirty four women veterans with chronic pain and comorbid depression and/or posttraumatic stress disorder (PTSD) were recruited. Five sessions of education/therapy were delivered via telemedicine in combination with daily home practice of a portable biofeedback device (Stress Eraser®, Helicor, New York, NY, USA). Participants responded to self‐report questionnaires at baseline, at posttreatment, and at 6‐week follow‐up. Daily practice logs were also maintained by participants. Results The clinical protocol was acceptable, easy to administer, and associated with statistically significant decreases in self‐reported pain unpleasantness, pain interference, depressive symptoms, PTSD symptoms, and sleep disturbance at posttreatment. Improvements were maintained at 6‐week follow‐up. Qualitative analyses indicated that many participants 1) wished to continue to meet as a support group in their respective CBOCs and 2) felt less isolated and more empowered to cope with their problems of daily living as a result of the treatment. Conclusions It is feasible to provide treatment to women veterans living in rural areas by utilizing video‐teleconferencing technology between larger VA medical centers and facilities at CBOCs in more rural settings. A controlled trial of the intervention is warranted.